Microbial toxicity and impacts on soil enzyme activities of pesticides used in potato cultivation - Niemi, R. Maarit; Heiskanen, Ilse; Ahtiainen, Jukka; Rahkonen, Anne; Mäntykoski, Keijo; Welling, Leena; Laitinen, Pirkko; Ruuttunen, Pentti (Elsevier Science, 2009)
Abstract: In the conventional Cultivation of potatoes, weed control and the control of potato late blight caused by Phytophthora infestans are carried out by the application of herbicides and fungicides. We investigated the impacts of the herbicides metribuzin and linuron and the fungicide fluazinam oil soil microbiota in microcosms, in mesocosms and in the field. The toxicity of each pesticide in Solution was assessed using the luminescent bacteria test and in soil by a solid phase modification. In microcosm tests, the microbial activity and biomass were estimated by measuring several soil enzyme activities together with soil ATP content. In the mesocosm tests, the separate addition of each pesticide and the Simultaneous use of all the pesticides were investigated. We monitored the impacts on ten different soil enzyme activities and Measured soil toxicity with the luminescent bacteria test separately in the 5 cm top layer and in the layer from 5 to about 20 cm below the surface. During one season, the impact of the use of pesticides was monitored in the field in plots receiving pesticides for the third consecutive year and in control plots Cultivated without the use of pesticides for the 3 preceding years. The pesticide concentrations were monitored in each experiment. The luminescent bacteria toxicity test revealed a strong inhibition by fluazinam. In microcosms the herbicides increased several enzyme activities but metribuzin inhibited luminescence in the bacterial test. Fluazinam was highly toxic in microcosms. In the mesocosm with combined use of pesticides, decreased activities of some enzymes were observed first in the surface soil and at harvesting also deeper in the soil. In the mesocosm experiment with separate use of pesticides, less impacts were observed. In the field experiment the pesticides decreased seven enzyme activities, when calculated per soil fresh weight but activities of four enzyme decreases if calculated per soil organic matter. Controlling weeds by herbicides decreased weed growth and the decreases in enzyme activities were interpreted to be due to the lack of the stimulating impact of weed roots. A strong inhibition in the soil toxicity test and continuing bioavailability of fluazinam were detected throughout the experiments even after winter in the field. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Ta; metributsiini; linuron; peruna; perunanviljely; kasvinsuojelu; pestisidit; potatoes; plant protection; pesticides; metribuzin; linuron; microbial effects; soil enzyme activities; luminescent bacteria test; fluazinam; potato cultivation